Antimicrobial Candidate From Ethanol Extract And Ethyl Acetate Fraction Of Betadin (Jatropha multifida L.) Leaves Which Actively Inhibits Clinical Isolates Of Human Skin Pathogenic Bacteria And Fungi - Faroliu, Goldha; Adriani, Nova; Wulandari, Sarah (Universitas Bhakti Kencana, 2025)
Betadin leaf (Jatropha multifida L.) is an ornamental plant in Indonesia and is rarely used, but its leaf sap has been reported to accelerate wound healing due to skin infections. This has the potential to be used for the development of new antimicrobial agents. The extraction method was carried out by maceration using 96% ethanol and fractionation with ethyl acetate. Extracts and fractions analyzed for the presence of various phytochemical constituents. Antibacterial assay used disc diffusion (Kirby-Bauer's) method towards Propionibacterium acnes, Staphylococcus epidermidis, Corynebacterium diphtheriae, Microsporum canis and Epidermophyton floccosum. Ethanol extract of Betadin leaves contained Alkaloids, Flavonoids, Phenolics, Steroids, Terpenes, Saponins, while the ethyl acetate fraction contained Alkaloids, Phenolics, Terpenes. J. multifida leaf ethanol extract has strong activity towards Microsporum canis and Epidermophyton floccosum, and has weak activity towards Propionibacterium acnes, Staphylococcus epidermidis, and Corynebacterium diphtheriae. While J. multifida leaf ethyl acetate fraction has strong activity towards Propionibacterium acnes, Microsporum canis and Epidermophyton floccosum, and has weak activity towards Staphylococcus epidermidis, and Corynebacterium diphtheriae. Based on the results of this study can be concluded that both the ethanol extract and the ethyl acetate fraction of Betadin leaves (Jatropha multifida L.) had the ability to inhibit the growth of bacteria and fungi, then can be antimicrobial candidate of herbal medicine